Strategi Pendidikan Budi Pekerti - Rokhman, Anton Nur; Misbah, M (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
character education in schools is influenced by the existence of teachers as role models for students, teachers do not just teach subjects, teachers should be creative in educating students. In between delivering lessons the teacher also conveys positive values and norms, so that students are not only equipped with knowledge but also manners. If parents at home are figures of noble character, teachers at school become role models. Regarding the duties and role of the teacher in character education, teachers are required to be able to provide nuances that do not just convey knowledge, but can change the behavior of students to become virtuous human beings. This study is a qualitative descriptive study with a phenomenological approach